Sensitivity analysis of machine components thermal properties effects on winding temperature - Zhang, Fengyu; Gerada, David; Xu, Zeyuan; Zhang, He; Gerada, Chris (2019)
This paper investigates the sensitivity analysis of winding temperature to key parameters in electrical machine thermal design. With a validated 3D thermal model based on an existing 75kW traction machine for an electric vehicle, the methodology of the sensitivity analysis study is conducted and presented. Finally, further research and practical guidelines on reducing the peak temperature of electrical machines are proposed.